DEVELOPING THE ABILITY TO RECOGNIZE CAUSE AND EFFECT USING THE PROJECT BASED LEARNING MODEL AND SCIENCE EXPERIMENT METHOD IN GROUP B CHILDREN OF KHADIJAH PLUS ISLAMIC KINDERGARTEN BANJARMASIN - Napisah, Nurul Laila; Anggreani, Chresty (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The problem in this study is the low ability of children to recognize cause and effect, this is due to learning activities using LKPD and the use of models and methods that are less varied and monotonous. This study aims to describe the activities carried out by teacher and analyze children's activities, analyze the results of the development of the ability to recognize cause and effect. The data collection are observation, interview and documentation. The subject used in the study was group B of Khadijah Plus Islamic Kindergarten Banjarmasin. This research was carried out in two cycles and each cycle consisted of three meetings. The results of the study show that using the project based learning model and science experiment methods can improve children's ability to recognize cause and effect, as evidenced by the teacher's activity in the first cycle obtained an average score of 72 with good criteria, children's activities obtained a percentage of 74% of the active criteria, then for the ability to recognize cause and effect obtained a percentage of 72% of the criteria developed as expected. Then in the second cycle, the teacher got an average score of 84 with very good criteria, children's activities obtained a percentage of 98% of the very active criteria, then for the ability to recognize cause and effect obtained a percentage of 100% of the very good development criteria (BSB).